Atomistic simulation of epitaxial Si film growth on Si (001) surface - Xie, Xuepeng. (2008)
The purpose of this thesis is to study the effect of conditions such as substrate orientation, process temperature, atomic beam energy, thermal dissipation rate and deposition rate on the energetic and microstructure of epitaxial growth of silicon on Si (001) surface.